QUALITATIVE INTERPRETATION OF MAGNETIC MAPS AND GEOPHYSICAL SURVEYING OF LATE ROMAN SITES - Bondar, K. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Many years of experience in geophysical survey on archaeological sites confirmed by excavation results led us to develop the basic principles and criteria for qualitative interpretation of magnetic anomalies on Late Roman sites. Data have been obtained from high-resolution magnetic surveys of settlements and burial grounds dating back to the 2nd – first half of the 5th century AD across a wide geographic range – from Bukovyna to the Left bank of the Dnieper. Magnetic studies were conducted on four settlements and four burial grounds belonging to the Cherniakhiv culture, including the Komariv burial ground and settlement site (Chernivtsi region), the Malopolovetske-2A settlement site (Kyiv region), the Chervone-2 burial ground (Kyiv region), the Legedzyne burial ground (Cherkassy region), the Dmytrivka-3 settlement site (Poltava region) and the Viytenky-1 burial ground and settlement site (Kharkiv region). Maps of induced magnetic anomalies were produced based on the results of field measurements using cesium magnetometers with 0.001 nT resolution. Processing and calculation of magnetic field anomalies were followed by generating a regular mesh (0.25x0.25 m). The types of magnetic anomalies associated with archaeological sites are determined by the following factors: size, intensity, positive/negative/alternating character, and the location of the negative part of an alternating anomaly relative to magnetic north. The results of measurements and excavations on the Late Roman sites show that it is feasible to focus on a few types of magnetic anomalies when interpreting magnetic maps. Archaeological artefacts may account for weak (2…15 nT) positive anomalies covering areas of over 1 m2 on a settlement site. These tend to form over shallow housing – dugouts, as well as over massive ground dwellings, covered with a minimum of 1.5 mthick layer of soil (e.g. due to soil deposited from the slope). Alternating anomalies with the positive part having an isometric shape and covering an area of 4 m2 are also common on Late Roman settlement sites. The intensity of these anomalies can range from 5 to 100 nT or more, with the negative part always located on the north side. Such anomalies tend to form over furnaces and kilns. Magnetic surveys on Late Roman burial sites only yielded reliable data on the anomalies associated with deep ground "princely" inhumation burials. The corresponding anomalies have intensity of up to 7 nT and cover areas of 3…8 m2. These form due to a difference in magnetization of the material filling the pit and that of the surrounding parent rock.